2019
DOI: 10.1186/s41155-019-0121-8
|View full text |Cite
|
Sign up to set email alerts
|

Facial expressions and eye tracking in individuals with social anxiety disorder: a systematic review

Abstract: Social anxiety disorder (SAD) is characterized by the fear of being judged negatively in social situations. Eye-tracking techniques have been prominent among the methods used in recent decades to investigate emotional processing in SAD. This study offers a systematic review of studies on eye-tracking patterns in individuals with SAD and controls in facial emotion recognition tasks. Thirteen articles were selected from the consulted databases. It was observed that the subjects with SAD exhibited hypervigilance-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 35 publications
0
12
0
5
Order By: Relevance
“…However, the authors could not affirm clear results of hypervigilance to threat-relevant stimuli, like angry faces, in VR. Relating to these results e Claudino et al (2019) call into question in their review the ecological validity of other studies, which indicated hypervigilance regarding emotions. Most research mainly used visual search and dot-probe tasks or measured gaze behavior (e.g., hypervigilance in time periods of 500-1500 ms) when persons looked at images of different faces on a computer display.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, the authors could not affirm clear results of hypervigilance to threat-relevant stimuli, like angry faces, in VR. Relating to these results e Claudino et al (2019) call into question in their review the ecological validity of other studies, which indicated hypervigilance regarding emotions. Most research mainly used visual search and dot-probe tasks or measured gaze behavior (e.g., hypervigilance in time periods of 500-1500 ms) when persons looked at images of different faces on a computer display.…”
Section: Discussionmentioning
confidence: 95%
“…These mixed empirical results caused the formulation of a vigilance-avoidance hypothesis of selective attention (Bögels and Mansell, 2004;Wieser et al, 2009a,b;Chen and Clarke, 2017). It assumes that socially anxious humans guide their initial attention to emotionally threatening information (hypervigilance) and avoid the negative information subsequently (attentional avoidance) to reduce emotional distress (Bögels and Mansell, 2004;e Claudino et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Because anxiety is considered a composite feeling that is mainly affected by fear, when a person experiences anxiety, one can expect to see facial signs that depict fear. Furthermore, although the facial signs of anxiety are ambiguous and study results are inconsistent, anxiety’s effects on the face are thought to be related to alterations in eye movements, skin reddening, and lip distortions [ 44 ]. Anxiety is a critical emotion when considered in terms of individual differences in facial expression recognition [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…A second aim was to examine whether ASD traits were associated with social attention. Further, given that AN is also associated with high levels of depression (Godart et al 2015 ), anxiety (Kerr-Gaffney et al 2018 ; Swinbourne and Touyz 2007 ), and alexithymia (Westwood et al 2017a ), factors which may themselves alter socio-cognitive processes (Claudino et al 2019 ; Duque and Vázquez 2015 ; Frazier et al 2017 ; Fujiwara 2018 ; Gregory et al 2019 ), a third aim was to examine whether comorbid psychopathology was associated with social attention. It was hypothesised that high levels of ASD traits would be associated with less time spent looking at faces and eyes, as well as a longer delay until first fixation on the face.…”
mentioning
confidence: 99%